Образовната идеологија во Византија - Aneta Jovkovska (Институт за национална историја, Скопје, 2022)
In Byzantine society, which throughout its thousand-year history has followed the path of eternal salvation, the word “culture” also meant “education, teaching and upbringing in order to lead a certain way of life.” Byzantine theologians have always had a deep respect for knowledge and recognized the special value of education, and above all they valued knowledge in the field of grammar and rhetoric. Without such knowledge, they argued, it was impossible to understand the Scriptures, to acquire the skills to argue with pagans and heretics, and even more to create original works in the field of spiritual literature. It is important to note that Byzantine education, unlike Western education, was not in the hands of the church. Although certain ecclesiastical disciplines were taught in Byzantine schools, they remained generally secular. The education system itself was very reminiscent of the ancient. Therefore, the gradual disappearance of pagan beliefs did not contribute to the disappearance of ancient literature and philosophy. They have passed through the centuries and survived to our time.
Educational ideology in Byzantium